OncomiRs as noncoding RNAs having functions in cancer: Their role in immune suppression and clinical implications - Otmani, Khalid; Rouas, Redouane; Lewalle, Philippe (Frontiers in Immunology, 2022)
Currently, microRNAs have been established as central players in tumorigenesis, but above all, they have opened an important door for our understanding of immune and tumor cell communication. This dialog is largely due to onco-miR transfer from tumor cells to cells of the tumor microenvironment by exosome. This review outlines recent advances regarding the role of oncomiRs in enhancing cancer and how they modulate the cancer-related immune response in the tumor immune microenvironment. MicroRNAs (miRNAs) are a type of noncoding RNA that are important posttranscriptional regulators of messenger RNA (mRNA) translation into proteins. By regulating gene expression, miRNAs enhance or inhibit cancer development and participate in several cancer biological processes, including proliferation, invasion metastasis, angiogenesis, chemoresistance and immune escape. Consistent with their widespread effects, miRNAs have been categorized as oncogenes (oncomiRs) or tumor suppressor (TS) miRNAs. MiRNAs that promote tumor growth, called oncomiRs, inhibit messenger RNAs of TS genes and are therefore overexpressed in cancer. In contrast, TS miRNAs inhibit oncogene messenger RNAs and are therefore underexpressed in cancer. Endogenous miRNAs regulate different cellular pathways in all cell types. Therefore, they are not only key modulators in cancer cells but also in the cells constituting their microenvironments. Recently, it was shown that miRNAs are also involved in intercellular communication. Indeed, miRNAs can be transferred from one cell type to another where they regulate targeted gene expression. The primary carriers for the transfer of miRNAs from one cell to another are exosomes. Exosomes are currently considered the primary carriers for communication between the tumor and its surrounding stromal cells to support cancer progression and drive immune suppression. Exosome and miRNAs are seen by many as a hope for developing a new class of targeted therapy. This review outlines recent advances in understanding the role of oncomiRs in enhancing cancer and how they promote its aggressive characteristics and deeply discusses the role of oncomiRs in suppressing the anticancer immune response in its microenvironment. Additionally, further understanding the mechanism of oncomiR-related immune suppression will facilitate the use of miRNAs as biomarkers for impaired antitumor immune function, making them ideal immunotherapy targets.